1997
DOI: 10.1523/jneurosci.17-18-07129.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Polysynaptic Feedback Circuit in Rat Visual Cortex

Abstract: Feedback connections from extrastriate cortex to primary visual cortex (V1) in the primate may provide "top-down" information that plays a role in visual attention and object recognition. Our work in a rodent model of corticocortical circuitry demonstrates that feedback pathways synapse preferentially with pyramidal cells in V1 (Johnson and Burkhalter, 1996) and favor excitation over inhibition in cortical microcircuits .To investigate the polysynaptic circuits activated by feedback inputs, we studied chains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 58 publications
12
72
0
Order By: Relevance
“…In particular, we observed a reduction in number of the long range corticocortical connections crossing the lesion in contrast with the preservation of the short range ones. Since short-range connections of pyramidal cells are supposed to be less inhibitory than the long-range connections [19], we hypothesized that the relative lack of long-range fibers in our animals might unbalance excitatory and inhibitory cortical signals in favor of excitability. Thus, a hyperexcitability of the region could be established even when the number of inhibitory interneurons in these areas is preserved, as shown by recent investigations [20].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we observed a reduction in number of the long range corticocortical connections crossing the lesion in contrast with the preservation of the short range ones. Since short-range connections of pyramidal cells are supposed to be less inhibitory than the long-range connections [19], we hypothesized that the relative lack of long-range fibers in our animals might unbalance excitatory and inhibitory cortical signals in favor of excitability. Thus, a hyperexcitability of the region could be established even when the number of inhibitory interneurons in these areas is preserved, as shown by recent investigations [20].…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be because axons responsible for antidromic activation are further away from the stimulating electrode. However, we have found that FB axons often synapse on FF-projecting neurons (Johnson and Burkhalter, 1997) and FF fibers contact FB-projecting cells (A. Burkhalter, unpublished observations), suggesting that fibers for potential orthodromic and antidromic activation are intermingled.…”
Section: Feedforward Inhibition Of Pyramidal Neurons By Ff and Fb Inputsmentioning
confidence: 95%
“…Thus, it appears that strong (Yamashita et al, 2003;Fig . 1D) and highly effective (Cauller and Connors, 1994;Larkum and Zhu, 2002) FB input to apical dendrites in layer 1 (Johnson and Burkhalter, 1997), which is lacking in the FF pathway (Yamashita et al, 2003), may compensate for sparser input to layer 2/3.…”
Section: Pathway Difference In the Strength Of Synaptic Inhibitionmentioning
confidence: 99%
“…FF and FB inputs to layer 2/3 of rat V1 and LM synapse mainly onto spines of Pyr cells (Johnson and Burkhalter, 1996). In the FB LM3V1 pathway most of these are FF V13LM -projecting Pyr cells (Johnson and Burkhalter, 1997). Similarly, FF inputs preferentially synapse onto FB LM3V1 -projecting Pyr cells.…”
Section: Target Neurons Of Synaptic Ff and Fb Inputs Layer 2/3mentioning
confidence: 99%